2022
DOI: 10.1002/asia.202101337
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescent ABC‐Triblock Polymer Nanocarrier for Cisplatin Delivery to Cancer Cells

Abstract: Monitoring intracellular administration of nonluminescent anticancer drugs like cisplatin is a very challenging task in cancer research. Perylenebisimide (PBI) chromophore tagged fluorescent ABC-triblock polycaprolactone (PCL) nanoscaffold was engineered having carboxylic acid blocks for the chemical conjugation of cisplatin at the core and hydrophilic PEG blocks at the periphery. The amphiphilic ABC triblock Pt-prodrug was self-assembled into < 200 nm nanoparticles and exhibited excellent shielding against dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…The amphiphilicity was then introduced into PBI-Poly12 by the hydrolysis of t Bu groups of P-( t BuCL) block to COOH groups, which can easily be transformed into nanoassemblies in water, useful for delivery application. 57…”
Section: S C H E M E 2 (A-e)mentioning
confidence: 99%
See 2 more Smart Citations
“…The amphiphilicity was then introduced into PBI-Poly12 by the hydrolysis of t Bu groups of P-( t BuCL) block to COOH groups, which can easily be transformed into nanoassemblies in water, useful for delivery application. 57…”
Section: S C H E M E 2 (A-e)mentioning
confidence: 99%
“…Both the PBI-CPCL-PEGPCL and PBI-CPCL-PEGPCL-Pt conjugates were applied for fluorescence imaging of HeLa, MCF 7, and WT-MEF cells (Scheme 6). 57 Yu et al 61 reported the use of noncytotoxic NMI endcapped PDMAEMA (NMI-Poly2, Figure 1) conjugates with strong blue and green fluorescence for imaging as well as specific tracking of lysosomes in a representative HeLa cell line. These conjugates can also be used for monitoring the pH changes occurring in lysosomes under different experimental conditions (Figure 1).…”
Section: Biological Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This emphasized the need for developing new unimolecular micelle nanoassemblies in a fully biodegradable polymer platform that would open a new avenue of opportunities in cancer research. For the past decade, our research group has been exploring carboxylic functionalized PCL-based di- and triblock copolymers for delivering a cocktail of DOX and cisplatin for synergistic combination therapy in breast cancer cell lines. , Fluorescent labeled PCL block copolymers were also developed to study the intracellular enzymatic-biodegradation aspects of the PCL backbone by the FRET mechanism. Biodegradable cationic PCL nanoassemblies were also made, and their fluorescent-cum-antimicrobial action was studied in detail in Escherichia coli . This experience helped us to design one of the first examples of fully biodegradable star block copolymers based on a hydrophobic PCL core and a carboxylic acid-substituted hydrophilic PCL shell as shown in Figure .…”
Section: Introductionmentioning
confidence: 99%
“…Tweaking the topology of the macromolecular architectures was found to be very crucial factor in designing the star-UMM. For this purpose, hydrophobic polycaprolactone (PCL) and carboxylic substituted hydrophilic PCL segments were chosen based on our expertise in cancer research [44][45][46][47][48][49][50][51][52][53] and systematically several structures such as linear di-blocks, star di-blocks, and star random copolymers were tailor-made by ring opening polymerization (ROP) to get the right polymer geometry with high encapsulation capabilities. The in vivo biodistribution data established the supremacy of the star-UMM platform for crossing the BBB with reduced side-effect of cardiotoxicity.…”
Section: Introductionmentioning
confidence: 99%